Phraseologism as a Linguistic Phenomenon - Primova Munisa Majlim qizi (Zien Journals, 2023)
In this article, phraseologism as a linguistic phenomenon is theoretically analyzed. The peculiarity of phraseologisms is that they reflect the main features of the language at different levels. The lexicon or phraseology serves as the basis for phraseological units. Phraseological units are formed from mutual association of words. Therefore, the peculiarity of comparative phraseological analysis arises from the need to take into account the primary systems - lexicon and grammar, as well as the features of their manifestation in phraseology.
Keywords: proverbal phraseology; phenomenon; phraseology; syntagmatic construction.